Knowledge and practice mobilities in the process of policy-making: The case of UK national well-being statistics. (January 2017) - Jenkins, Matt
Abstract: This paper examines the creation of the UK's 'Measuring National Well-being' statistical programme, drawing on accounts given of the creation of the programme in official sources and primary interviews. Focusing on the microspaces of public consultations and advisory panels, it argues that the construction of this statistical object was simultaneously the construction of a knowledge-object for academics and of a policy-object for policy-makers. As such, the statistic drew on and fed into domestic and international networks of statistical, academic and policy usage. The programme was shaped by the needs of these multiple networks, creating an object that they could hold in common but which did not necessarily fully satisfy any of them. Understanding the creation of objects in this way extends understandings around policy transfers and mobilities by showing how policy-objects arise through the transfer and mobility of things which are not policy. Simultaneously, what arises from policy mobility is not simply policy. Instead, what arises is multiple objects, which are the product of the intersection of travelling policy, knowledge and practice and they feed back into existing networks of knowledge, policy and practice. In doing so, the paper shows the inter-relations of knowledge and practice with policy, revealing them to be situated in place, contingent and compromised. It also contributes to the understanding of how official statistics, as a key technology of the state, are created. Highlights: Examines the creation of official statistics, a previously under-examined area. Illustrates the microspace approach to exploring policy mobilities. Extends models of policy construction by examining how knowledge- and practice-objects are created simultaneously with policy-objects. Extends models of policy mobility by showing the influence of non-policy networks, and the corresponding influence the policy-object has on these networks.